NSUN2 Promotes Tumor Progression and Regulates Immune Infiltration in Nasopharyngeal Carcinoma - Tong, Xinya; Xiang, Yilan; Hu, Yuanbo; Hu, Yingying; Li, He; Wang, Huilin; Zhao, Kong-Nan; Xue, Xiangyang; Zhu, Shanli (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is one of the most common malignancy in head and neck with a complex etiology, such as environmental factors, genetic factors, Epstein-Barr virus infection. NOP2/Sun domain family, member 2 (NSUN2) is a methyltransferase of m5C methylation modification, which has been reported to be involved in the occurrence and progression of various tumors, but its role in NPC remains unclear. Here, we found that NSUN2 were upregulated in NPC and predicted a poor prognosis of NPC patients in both GEO datasets and our tissue microarrays containing 125 NPC tissues. Next, we demonstrated that NSUN2 promoted the proliferation, migration, and invasion of NPC cells in vitro. In addition, the differential expression genes between NSUN2-high and low expression patients were mainly enriched in multi-immune cells activation and proliferation. Furthermore, NSUN2 negatively regulates immune cell infiltration in the tumor microenvironment (TME) of NPC, which indicates that the NSUN2 level may be negatively correlated with the sensitivity of immunotherapy and chemotherapy. In conclusion, our findings highlighted that NSUN2 might acted as an important oncogene involved in NPC progression, and serve as a potential biomarker to predict poor prognosis and drug sensitivity of NPC patients.